2018
DOI: 10.1002/hrm.21909
|View full text |Cite
|
Sign up to set email alerts
|

Effects of training and development on employee outcomes and firm innovative performance: Moderating roles of voluntary participation and evaluation

Abstract: This study investigates the effect of training and development (T&D) on firm innovation. Given the inconsistent findings on the performance implications of T&D and the lack of studies on the T&D-innovation relationship, we elaborate the multiple dimensions of T&D, intermediate employee outcomes, and boundary conditions to elucidate the pathways of T&D toward firm innovation. We specifically identify two distinct T&D dimensions, namely, firm investment and employees' positive perceptions. The former and the lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 57 publications
(135 reference statements)
0
51
1
3
Order By: Relevance
“…To address the gap between the prevailing assumption and mixedempirical evidence on the value of T&D, the present study investigatesthe distinct functions associated with different dimensions of T&D, their intermediate employee outcomes (Sung, & Choi, 2018). The outcomes of this research will help and support the banks to identify the Training and Developmentfactors that influence the employee performance in the banking organizations.…”
Section: Significance Of the Studymentioning
confidence: 97%
See 1 more Smart Citation
“…To address the gap between the prevailing assumption and mixedempirical evidence on the value of T&D, the present study investigatesthe distinct functions associated with different dimensions of T&D, their intermediate employee outcomes (Sung, & Choi, 2018). The outcomes of this research will help and support the banks to identify the Training and Developmentfactors that influence the employee performance in the banking organizations.…”
Section: Significance Of the Studymentioning
confidence: 97%
“…Training and developmentis refers to "a series of organized activities conducted within a specified time and designed to produce behavioral change" (Sung, & Choi, 2018).…”
Section: Training and Developmentmentioning
confidence: 99%
“…Prior research has also suggested that HPWS may generate the capacity for innovation (Do, Budhwar, & Patel, 2018; Fu, Flood, Bosak, Morris, & O'Regan, 2015; Sung & Choi, 2018). While HPWS do not themselves constitute a source of competitive advantage, they may serve to generate a unique set of HRM attributes to do so (Beugelsdijk, 2008; Colbert, 2004; Patel, Messersmith, & Lepak, 2013).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Specific bundles, for example, may be directed at either the external acquisition of human capital (e.g., selective staffing and compensation strategies to attract high quality talent) or towards development of talent internally (e.g., training, performance management, internal promotion, job rotation, etc. ; Soo, Tian, Teo, & Cordery, 2017; Sung & Choi, 2018). Similarly, appropriate reward and recognition policies and practices also provide a strong system effect through guiding and rewarding adaptive employee behaviours (Bhattacharya, Gibson, & Doty, 2005; Tzabbar, Tzafrir, & Baruch, 2017) or through reshaping the psychological contract between employees and the firm (Bowen & Ostroff, 2004).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…The positive effect of training is at least two mechanisms, namely improving knowledge and skills related to employee work, as well as employee who receives the benefits can be rewarded with increased effort and commitment. (Sung &Choi, 2018). Training indicates that the organization is willing to invest in its employees and the promotional opportunities signal that the organization recognizes and appreciates the contributions of its employees.…”
Section: Findings and Discussionmentioning
confidence: 99%